Integrasi Sistem Pengawasan Dps Terhadap Lks Bmt Ugt Nusantara Kabupaten Situbondo - Makki, Mustaqim; Sa’diyah, Sakinatus (INAIFAS Press, 2021)
The integration of the supervisory system at BMT UGT Nusantara (originally named BMT Sidogiri) by DPS has three supervisors, namely management supervisors, sharia supervisors, and financial supervisors. The three supervisors are both walking or supervising according to their respective positions. The supervision carried out by DPS on BMT Nusantara in Situbondo is integrated in one branch, so that the effectiveness of the supervision performance is one-stop integrated. The supervision of the work system of sharia financial institutions is usually carried out for six months once to the existing branches of BMT UGT Nusantara, but in this supervision the Sharia Supervisory Board (DPS) does not always go directly to conduct supervision, either in terms of products, contracts and so on, but the Sharia Supervisory Board (DPS) formed a sharia team devoted to controlling the existing branches of BMT UGT Nusantara. The supervision of the Sharia Supervisory Board (DPS) is unified in several branches due to the decision of the central management, in which the merging of several branches into one Sharia Supervisory Board (DPS) is not an obstacle in its supervision.